Midkine Is Elevated After Multiple Trauma and Acts Directly on Human Cardiomyocytes by Altering Their Functionality and Metabolism - Lackner, Ina; Weber, Birte; Baur, Meike; Haffner-Luntzer, Melanie; Eiseler, Tim; Fois, Giorgio; Gebhard, Florian; Relja, Borna; Marzi, Ingo; Pfeifer, Roman; Halvachizadeh, Sascha; Lipiski, Miriam; et al. (Frontiers in Immunology, 2019)
Background and Purpose: Post-traumatic cardiac dysfunction often occurs in multiply injured patients (ISS 16). Next to direct cardiac injury, post-traumatic cardiac dysfunction is mostly induced by the release of inflammatory biomarkers. One of those is the heparin-binding factor Midkine, which is elevated in humans after fracture, burn injury and traumatic spinal cord injury. Midkine is associated with cardiac pathologies but the exact role of Midkine in the development of those diseases is ambiguous. The systemic profile of Midkine after multiple trauma, its effects on cardiomyocytes and the association with post-traumatic cardiac dysfunction remain unknown. Experimental Approach: Midkine levels were investigated in blood plasma of multiply injured humans and pigs. Furthermore, human cardiomyocytes (iPS) were cultured in presence/absence of Midkine and analysed regarding viability, apoptosis, calcium handling, metabolic alterations and oxidative stress. Finally, the Midkine filtration capacity of the therapeutic blood absorption column CytoSorb300 was tested with recombinant Midkine or plasma from multiply injured patients. Key Results: Midkine levels were significantly increased in blood plasma of multiply injured humans and pigs. Midkine acts on human cardiomyocytes, altering their mitochondrial respiration and calcium handling in vitro. CytoSorb300 filtration reduced Midkine concentration ex vivo and in vitro depending on the dosage. Conclusion and Implications: Midkine is elevated in human and porcine plasma after multiple trauma, affecting the functionality and metabolism of human cardiomyocytes in vitro. If the application of CytoSorb300 filtration for patients after multiple trauma is a promising therapeutic approach to prevent post-traumatic cardiac dysfunction requires further examination.